2014
DOI: 10.1021/jp408241f
|View full text |Cite
|
Sign up to set email alerts
|

Convective Flows in Evaporating Sessile Droplets

Abstract: The evaporation rate and internal convective flows of a sessile droplet with a pinned contact line were formulated and investigated numerically. We developed and analyzed a unified numerical model that includes the effects of temperature, droplet volume, and contact angle on evaporation rate and internal flows. The temperature gradient on the air/liquid interface causes an internal flow due to Marangoni stress, which provides good convective mixing within the droplet, depending upon Marangoni number. As the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 37 publications
1
37
0
Order By: Relevance
“…12. This indicates a rather constant evaporation rate throughout drying which is in correspondence with observations by Ruiz and Black [6] and Barmi and Meinhart [12]. The increased heat and mass transfer rates obtained at smaller contact angles might thus be balanced out by decreased surface area and internal conduction.…”
Section: Coupling Of Internal and External Flowsupporting
confidence: 88%
“…12. This indicates a rather constant evaporation rate throughout drying which is in correspondence with observations by Ruiz and Black [6] and Barmi and Meinhart [12]. The increased heat and mass transfer rates obtained at smaller contact angles might thus be balanced out by decreased surface area and internal conduction.…”
Section: Coupling Of Internal and External Flowsupporting
confidence: 88%
“…Numerical simulations have confirmed high evaporative flux at the contact line of the thin-film region (Barmi and Meinhart, 2014;Deegan et al, 1997Deegan et al, , 2000Yunker et al, 2011). Because of this, salt supersaturation increases close to the corners creating a chemical potential difference inside the trapped brine.…”
Section: Microscopic Viewmentioning
confidence: 81%
“…They used spatial profile of evaporation mass flux described by Hu and Larson [2] in their model and showed that the spatial profile of temperature at the liquid-gas interface depends on the ratio of thermal conductivity of the substrate to that of the droplet. Simulations by Barmi and Meinhart [10] quantified the internal convection against Marangoni number and they found that the Marangoni convection becomes negligible as the droplet volume decreases during the evaporation.…”
Section: Introductionmentioning
confidence: 99%